Demonstrasi Plot Pupuk Organik Cair (POC) Sabut Kelapa dan Batang Pisang di KWT Banda Langik - Nalwida Rozen; Nurwanita Ekasari Putri; Aries Kusumawati; Ryan Budi Setiawan; Fitri Ekawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
The community service took place for the Women Farming Group (WFG) of Banda Langik in the Sungai Bangek, Balai Gadang, Koto Tangah District, Padang City, from July to November 2022. It was held in demonstration plots (dump lots) of Liquid Organic fertilizers (LOF) with coconut coir, and banana stems as raw materials. These raw materials were straightforward to find in this area. Plots were made of 2 beds, and each was planted with pull-out Kale from seeds. Each bed was divided into two parts: without LOF and given LOF. It helped the WFG members differentiate the growth and yield pull-out Kale between being given LOF and without LOF. LOF was made by fermenting coconut coir separately and banana stems in a closed bucket for two weeks. The fermented products were sprinkled on the plants every week, starting at the age of two weeks after planting until they were close to harvest. The results showed that the plants given LOF were higher than those without LOF. The plant has given LOF more leaves. Their length and width of leaves were more significant than those without LOF. LOF is very useful given to vegetable plants, especially pull-out Kale.